The dozing shaman : the Limbus of eastern Nepal - Sagant, Philippe; Scott, Nora B. (New Delhi : Oxford University Press, 2008)
Collection of articles.
1. izd.: 1996.
Bibliografija: str. [447]-455 i kazalo
Keywords: Religious life and customs; Tāplejung (Nepal); religija i običaji; nepalski šamanizam; narod Limbus - Nepal -- etnologija